14.2k views
4 votes
HURRYYY

Which expression is equivalent to E
1 (3),
n=10
15
15
3
Ση + Σ
=10 η = 10
31
O
15
15
15
Ση + Σ3 - Ση
h=10
h=10
η=10
15
3
Ο η Σ
η
η =10
Σ
8
15
3
Ση
η
η=10

HURRYYY Which expression is equivalent to E 1 (3), n=10 15 15 3 Ση + Σ =10 η = 10 31 O-example-1
User Shutefan
by
5.7k points

1 Answer

3 votes

Answer:

the first one

Explanation:

it is really easy to see in this case.

the main formula is just a sum of a sum.

anything you just add you can split in its parts and then sum it all up - it is still the same.

so, the sum of (n + 3/n) can be split without any additional tricks into the sum of n and the sum of 3/n, and then add both results together.

the second option is wrong, because a division cannot be split like an addition. just try the first two elements (n=10 and n=11) for the simplified formula of the sum of (3/n). 3/10 + 3/11 is definitely not the same as (3 + 3) / (10 + 11).

the third and fourth option are already disqualified, because "n" assists outside of the sum operation (but "n" is only defined inside of it).

User Loopmasta
by
5.8k points